2014
DOI: 10.4141/cjas2013-126
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Tenderness of suckler beef produced in British Columbia

Abstract: Hartling, I., Cinel, B., Donkor, K. K., Ross Friedman, C., Paetkau, M. J. and Church, J. S. 2014. Short Communication: Tenderness of suckler beef produced in British Columbia. Can. J. Anim. Sci. 94: 295–298. In order to investigate the potential of suckler beef production in British Columbia, shear force values were determined using Warner–Bratzler shear (WBS) force tests on 10 major muscles obtained from suckler-raised Simmental cattle along with the longissimus thoracis from grain- and grass-fed cattle of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although less common in North America, suckler beef could potentially fill a health conscious or environmentally sustainable niche market by providing a diversified, low-input alternative to common high-grain finishing practices. Recently, we demonstrated that various muscles from suckler calves grazing on mountainous range pasture in British Columbia, Canada, had Warner Bratzler shear-force tenderness values lower than that of typical grain-fed beef in North America, suggesting that a greater proportion of the carcass could be marketed for a premium (Hartling et al 2014). In the same study, feeding a moderate grain diet to weaned calves for 100 d did not have a deleterious effect on meat tenderness values (Hartling et al 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although less common in North America, suckler beef could potentially fill a health conscious or environmentally sustainable niche market by providing a diversified, low-input alternative to common high-grain finishing practices. Recently, we demonstrated that various muscles from suckler calves grazing on mountainous range pasture in British Columbia, Canada, had Warner Bratzler shear-force tenderness values lower than that of typical grain-fed beef in North America, suggesting that a greater proportion of the carcass could be marketed for a premium (Hartling et al 2014). In the same study, feeding a moderate grain diet to weaned calves for 100 d did not have a deleterious effect on meat tenderness values (Hartling et al 2014).…”
mentioning
confidence: 99%
“…Recently, we demonstrated that various muscles from suckler calves grazing on mountainous range pasture in British Columbia, Canada, had Warner Bratzler shear-force tenderness values lower than that of typical grain-fed beef in North America, suggesting that a greater proportion of the carcass could be marketed for a premium (Hartling et al 2014). In the same study, feeding a moderate grain diet to weaned calves for 100 d did not have a deleterious effect on meat tenderness values (Hartling et al 2014). An evaluation of Spanish suckler beef production systems indicated greater economic returns in addition to producing meat with desirable organoleptic properties and a favorable fatty acid (FA) profile (Aldai et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation